2013
DOI: 10.1126/science.1230062
|View full text |Cite
|
Sign up to set email alerts
|

TERT Promoter Mutations in Familial and Sporadic Melanoma

Abstract: Cutaneous melanoma occurs in both familial and sporadic forms. We investigated a melanoma-prone family through linkage analysis and high-throughput sequencing and identified a disease-segregating germline mutation in the promoter of the telomerase reverse transcriptase (TERT) gene, which encodes the catalytic subunit of telomerase. The mutation creates a new binding motif for Ets transcription factors and ternary complex factors (TCFs) near the transcription start and, in reporter gene assays, caused up to two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

80
1,822
5
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,645 publications
(1,918 citation statements)
references
References 26 publications
80
1,822
5
11
Order By: Relevance
“…For example, both BRAF and EGFR mutations frequently co-occur with hTERT promoter mutations in melanoma and glioblastoma and may be necessary for GABPmediated activation prior to its interaction with the mutant hTERT promoter. 45,47,53 While both types of allelic changes could contribute to the activation of hTERT, we provide evidence here that a third mechanism, independent of genomic background, involves inactivation of the silencer element and is also an important contributor to the activation of hTERT. Critically, this finding also provides a direct opportunity to reverse the effects of these somatic mutations.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…For example, both BRAF and EGFR mutations frequently co-occur with hTERT promoter mutations in melanoma and glioblastoma and may be necessary for GABPmediated activation prior to its interaction with the mutant hTERT promoter. 45,47,53 While both types of allelic changes could contribute to the activation of hTERT, we provide evidence here that a third mechanism, independent of genomic background, involves inactivation of the silencer element and is also an important contributor to the activation of hTERT. Critically, this finding also provides a direct opportunity to reverse the effects of these somatic mutations.…”
Section: Introductionmentioning
confidence: 76%
“…51 Through a G-to-A mutation (G/A) in the antisense strand, hTERT promoter mutations are proposed to generate an ETS/TCF element (CCGGAA) that would increase binding of the ETS transcription factor for activation of hTERT transcription. 45,46 In addition, it has recently been suggested that the mutations found in glioblastoma multiforme could lead to recruitment of multimeric GA-binding protein (GABP) transcription factors to activate hTERT. 52 However, these models cannot fully account for promoterdriven hTERT transcriptional modulation in part because genetic background may play a role in enabling aberrant transcription factor binding.…”
Section: Introductionmentioning
confidence: 99%
“…Telomere size is mainly controlled by telomerase activity, and its abnormal reactivation is reported in up to 90 % of human tumors. Only recently, Huang et al [2] and Horn et al [5] showed that mutations in the promoter region of TERT gene, namely the c.-146:C>T and the c.-124:C>T mutations, generate a new consensus binding site for ETS/TCFs transcription factors (CCGGAA) leading to a two-to fourfold increase of the TERT promoter activity. The low frequency of TERT promoter mutations observed in our study raises evidence that other pathways may be involved in telomere regulation in TGCT.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key human cancer hallmarks is the abnormal upregulation of telomerase, that is codified by the telomerase reverse transcriptase (TERT) gene [1]. Recent studies identified the presence of hotspot somatic mutations in the promoter region of TERT gene, specifically the −124:C>T and −146:C>T mutations, in a range of human cancers such as bladder, gliomas, thyroid and melanoma [2][3][4][5]. These mutations have been shown to create a new binding motif sites for ETS transcription factors, which induces upregulation of TERT levels [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation